Giant Retroperitoneal Sarcoma: A Case Report and Review of Literature - Melissa K. Saad (International Journal of Recent Surgical and Medical Sciences, 2020)
Liposarcomas are neoplasms of mesodermal origin derived from adipose tissue representing 10 to 14% of all soft tissue sarcomas, with the most frequent subtype being liposarcoma. Given that the retroperitoneum is a large space in which the retroperitoneal liposarcoma can grow asymptomatically up until a mass effect develop. Hence, patients usually present late with symptoms with possible invasion to nearby structures. These tumors are known to reach significantly large dimension, despite their poor vascularization and can grow to enormous size, the average diameter of the tumor is 20 to 25 cm with a weight of 15 to 20 kg. Surgery with en-bloc resection of the tumor and adherent nearby structures, with intact capsule, remains the gold standard in surgical management of retroperitoneal sarcomas. Herein, we present a case of 52 year old male patient with a huge 48 cm right-sided retroperitoneal liposarcoma, managed surgically by en bloc excision of the tumor, right kidney, right ureter, right adrenal gland, and the right colon.